Pollution prevention the bottom line - Coastal Video Communications (Virginia : Coastal Video Communications, 1990)
Pollution prevention: it makes life for you, your family, your community and future generations better and perhaps possible. But pollution prevention is also good business
Keywords: Source reduction (Waste management); Waste minimization; Pollution